Additions and corrections to the cadastre of Orthoptera insects of Samarskaya Luka, on the basis of analysis of acoustic signals of males - Benediktov, Alexander А. (Nature Conservation Research: Заповедная наука, 2017)
For the territory of Samarskaya Luka, at the village Bakhilova Polyana (I.I. Sprygin Zhiguli State Natural Biosphere Reserve), 25 species of Orthoptera were found in mid-July 2016. These species were identified basically by the analysis of male acoustic signals. This is 44% of the total species composition of Samarskaya Luka Orthoptera, specified in the Cadastre of invertebrates of Samarskaya Luka. The specimens belonging to the grasshopper Platychleis albopunctata (= P. intermedia auct.) are clarified. The cricket Melanogryllus desertus and the locust Chorthippus dorsatus were found for the first time in the Samarskaya Luka. The species composition of the cryptic taxa of the «Chorthippus biguttulus group» of the Middle Volga region is discussed. Based on the unstable amplitude-time structure of the signals of the supposed Ch. biguttulus males from Malaya Bahilova Mountain, it is assumed that they may have a hybrid origin.